Studying the Effect of Dexamethasone and Water Extract Apricot on Experimental Chemical Corneal Ulcer in Rabbit - Abdalbari Abbas Alfaris (University of Thi-Qar Journal of Science, 2019)
The present study was designed to evaluate the effect of apricot and dexamethasone on rabbit eye ulcer. Bilateralcorneal ulcers were induced by a filter paper disk (4mm diameter) immersed with NaOH (1N) on central axis of corneain 20 rabbits. These animals were divided into two groups as follows; the first group, the corneal ulcer was treated withdexamethasone eye drops 0.1% twice daily while the second group, the corneal ulcer was treated with water extract ofapricot 2% twice daily.The clinical signs of corneal ulcer were evaluated by ophthalmoscope and fluorescent technique.After killing the animals, the corneas underwent routine histopathological examination on the 1st, 3rd and 5th day aftertreatment. Dexamethasone shows improvement in corneal ulcer through increasing the vascularization and infiltration ofcells; also it causes an increase in congestion in blood vessels but increases thickness epithelium while the apricot groupshows thick corneal epithelium associated with inflammatory cells. These findings indicate that apricot was good intreating for eye ulcer.